INTERACTIVE COMMUNICATION MEDIA IN THE MANAGEMENT OF SEXUAL VIOLENCE CASES IN HIGHER EDUCATION INSTITUTIONS IN INDONESIA (Journal of Namibian Studies : History Politics Culture, 2023)
Various forms of social violence continue to occur frequently, including in universities in Indonesia. Several efforts have been made to prevent and manage social violence, one of them is by issuing the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 30 of 2021. This regulation declares sexual violence as a public issue, prompting universities to be proactive in preventing and managing it. Numerous pertinent efforts have been made to support the implementation of this regulation. This study aims to describe interactive communication media in managing sexual violence cases in higher education institutions. It is qualitative research with a pragmatic approach. This method is not oriented toward a specific theory, but rather on an attempt to address a real-world problem. The data were collected through in-depth interviews, Focus Group Discussions (FGD), experiments, and documentation. The results of the study reveal that interactive communication media used in managing sexual violence cases in higher education institutions in Indonesia are categorized into four: (1) prevention media, (2) reporting media, (3) management media, and (4) volunteer media. As a result, an interactive communication model for preventing and managing sexual violence in higher education institution can be developed by considering the four critical elements of the Prevention and Management of Sexual Violence (PPKS), consisting of prevention, reporting, management, and volunteer networks.